The Personal Status Law (PSL) and Patriarchy in Saudi Arabia: A Critical Examination - Mas'odi, Mas'odi; Zer, Anees El (Syura: Journal of Law, 2025)
In 2022, Saudi Arabia introduced the Personal Status Law (PSL) as part of its Vision 2030 reforms, promoting it as a milestone for women’s rights, particularly in marriage, divorce, and custody. However, critical analysis suggests that the PSL maintains deeply entrenched patriarchal norms legitimized through conservative interpretations of Islamic jurisprudence. Despite claims of progress, the law’s ambiguous language and retention of male guardianship structures raise concerns about its substantive impact on gender equality. This study aims to critically examine the PSL not merely as a legal document but as a political and cultural instrument reinforcing hierarchical gender relations. Employing a qualitative approach grounded in feminist legal theory and socio-legal analysis, this research applies documentary analysis to the PSL text, ministerial decrees, human rights reports, and academic literature. Thematic content analysis is used to uncover discursive patterns that normalize gender bias. Findings reveal that the PSL functions as a strategic, symbolic reform rather than a transformative legal change. While it introduces limited rights—such as minimum marriage age and partial custody protections—it perpetuates male authority through legal ambiguity and judicial discretion. This study contributes to scholarly discourse by situating the PSL within broader frameworks of authoritarian governance and cultural patriarchy. It highlights the limits of legal empowerment when reforms are disconnected from societal transformation and grassroots engagement, offering insights into how state-led modernization can simultaneously promote and constrain women’s rights.